Reconstruction Of Upper Lid (A Case Report) - Khan, Prof. Masood Hasan; Haider, Dr. Mrs. T. Z. (Indian Journal of Plastic Surgery, 1982)
Infra orbital flap can be utilized directly for partial and total upper lid losses in old persons where the skin is loose and elastic.